Performance Evaluation of EOS-06 OCM-3 Chlorophyll-a Retrievals in Case-1 Waters - Chiranjivi Jayaram; Neethu Chacko; Rajdeep Roy; T. Devi Varaprasada Rao; P. V. Nagamani; T. V. S. Udaya Bhaskar; K. N. Babu; Prakash Chauhan (Journal of the Indian Society of Remote Sensing, 2026)

Asymmetric marine heat wave patterns in the two basins of the North Indian Ocean - Alankita Nag; Neethu Chacko; Debadatta Swain; K.K. Sandeep (Regional Studies in Marine Science, 2026)

Assessment of the New Sea Surface Wind Products from EOS-6 Scatterometer - Neethu Chacko; Chiranjivi Jayaram (Journal of the Indian Society of Remote Sensing, 2025)

Utilization of EOS-06 Observations in Tropical Cyclone Research: A Case Study on Cyclone Mocha - Neethu Chacko; Chiranjivi Jayaram; Mohammad Suhail; Devi Vara Prasad; P V Nagamani (Journal of the Indian Society of Remote Sensing, 2025)

Impact of Indian Ocean Dipole on the Arabian Sea tropical cyclone activity - Neethu Chacko; Karthik Balaguru (Climate Dynamics, 2025)

Assessing coastal water quality along Odisha using Landsat-8: Insights into seasonal and spatial variability - Neethu Chacko; Chiranjivi Jayaram (Journal of Earth System Science, 2025)

Solar dryer with double pass flat plate solar collector and carbon nanodots-coated absorber surface - Dhanapaul Selvaraj Aniesrani Delfiya; Suresh Amrutha; Pachareentavita Muhamed Ashraf; Subramani Murali; Kuruthukulam Chacko Neethu; George Ninan (Environmental Science and Pollution Research, 2024)

On the rapid weakening of super-cyclone Amphan over the Bay of Bengal - Neethu Chacko (Ocean Dynamics, 2023)

Exploring the Offshore Wind Resource Potential of India Based on Remotely Sensed Wind Field Data - Neethu Chacko (Journal of the Indian Society of Remote Sensing, 2022)

Anomalous Reduction of the Total Suspended Matter During the COVID-19 Lockdown in the Hooghly Estuarine System - Chiranjivi Jayaram; Rajdeep Roy; Neethu Chacko; Debadatta Swain; Ramunaidu Punnana; S. Bandyopadhyay; S. B. Choudhury; Dibyendu Dutta (Frontiers in Marine Science, 2021)
The impact of the coronavirus disease 2019 (COVID-19) lockdown in the Hooghly estuarine region, India is assessed using the total suspended matter (TSM) concentration. The estimation of TSM is performed using Landsat-8/operational land imager (OLI), and an intercomparison of TSM load during the pre-lockdown and lockdown periods is done. It is observed that during the lockdown period, TSM reduced by 30–50%. This is a significant observation considering the ecological balance of the region and the fact that it is home to the largest mangroves in the world. This change in suspended matter presumably reflects the influence of reduction in anthropogenic activities owing to the COVID-19 lockdowns, such as industries, closure of shipping activities (through less dredging), and brick kilns (through less sediment removal), which are generally the primary contributors in this region. Even though these observed changes are representative of the positive influence of the COVID-19 lockdown, its implications in estuarine biogeochemistry still remain poorly quantified. The decrease in TSM content may increase light penetration, thereby increasing the primary productivity. In addition, low sediment load reaching the Bay of Bengal could influence the carbon export due to reduction in ballasting effect as reported from this region. In summary, the influence of the COVID-19 lockdown on the biogeochemistry of the aquatic ecosystem appears rather complex than thought earlier and may vary regionally based on local hydrodynamics. The analysis elucidates the complex interplay of regional lockdown and its implication in modulation of local biogeochemistry. However, the relative importance of each process in the Hooghly estuary remains to be fully evaluated.

Differential chlorophyll blooms induced by tropical cyclones and their relation to cyclone characteristics and ocean pre-conditions in the Indian Ocean - Neethu Chacko (Journal of Earth System Science, 2019)

Estimation of Chlorophyll-a in Northern Coastal Bay of Bengal Using Landsat-8 OLI and Sentinel-2 MSI Sensors - Shukla Poddar; Neethu Chacko; Debadatta Swain (Frontiers in Marine Science, 2019)

Effect of Cyclone Thane in the Bay of Bengal Explored Using Moored Buoy Observations and Multi-platform Satellite Data - Neethu Chacko; Leimiwon Zimik (Journal of the Indian Society of Remote Sensing, 2018)

Variability of Total Suspended Matter in the Northern Coastal Bay of Bengal as Observed from Satellite Data - Neethu Chacko; Chiranjivi Jayaram (Journal of the Indian Society of Remote Sensing, 2017)

Evaluation of SARAL / AltiKa Measured Significant Wave Height and Wind Speed in the Indian Ocean Region - Chiranjivi Jayaram; Saurabh Bansal; A. Sai Krishnaveni; Neethu Chacko; V. M. Chowdary; D. Dutta; K. H. Rao; C. B. S. Dutt; J. R. Sharma; V. K. Dadhwal (Journal of the Indian Society of Remote Sensing, 2016)

An anomalous cooling event observed in the Bay of Bengal during June 2009 - Neethu Chacko; Muthalagu Ravichandran; Rokkam R. Rao; Sadananda Satheesh Chandra Shenoi (Ocean Dynamics, 2012)